The Role of Database Applications of Digital Archive Management in The Era of Society 5.0 - Marsofiyati; Eryanto, Henry; Usman, Osly; Faslah, Roni; Febriantina, Susan; Oktobisono, Anggriawan; Fadli, Ghifari Aminudin; Sulastri, Tita; Suparman, Ady Fahril; Nada, Shafwatun; Maharrizki, Alif (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
We will encounter many technologies in the 4.0 revolution era, such as cloud computing, artificial intelligence, the internet, 5G, digitalization, and big data. All of these technologies have potential in the world of education. Based on information about some of the problems faced by teachers at ASPAPI Member Vocational Schools in the DKI Jakarta area, they must be addressed as soon as possible as a solution to increasing knowledge, abilities, and skills in running database applications on digital archives as one of the development and utilization of information and communication technology in the Industrial Revolution 4.0 era and the 5.0 social era. Therefore, the community service team tries to offer solutions to these problems through the following main activities: 1) increasing the understanding and skills of ASPAPI Member Vocational High School teachers in the DKI Jakarta area, 2) increasing abilities in teaching and learning activities for digital archives, especially the use of database applications. The method used for providing training consists of planning, action execution, observation, and reflection. We generate an application called Dive Apps, where these apps can manage archives with a digitalization system and can also be used by teachers in archival learning.